2002
DOI: 10.1002/gcc.10061
|View full text |Cite
|
Sign up to set email alerts
|

Direct correlation between FRA3B expression and cigarette smoking

Abstract: Cytogenetic deletions and/or loss of heterozygosity (LOH) of the short arm of chromosome 3, often with a break at 3p14, are well documented in lung tumors. The coincidence of a chromosomal fragile site, FRA3B, at a common chromosomal breakpoint in lung cancer has suggested that fragility at this site may predispose to breakage that could contribute to multistep carcinogenesis. This idea is supported by the more recent finding that FRA3B maps within the FHIT (fragile histadine triad) gene, and that aberrant tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 40 publications
4
49
0
Order By: Relevance
“…21 It has also been shown that exposure to environmental carcinogens such as smoking and alcohol consumption increases the potential for chromosome breakage at fragile sites FRA3B and FRA16D in esophageal, non-small-cell lung and cutaneous squamous cancer. [21][22][23][24][25] Furthermore, we have recently described alterations on WWOX gene in 50% of oral squamous cell carcinomas. 26 Therefore, given that OLs have been associated with squamous carcinomas, we investigated whether molecular changes of the WWOX gene were present in these potentially malignant disorders.…”
Section: Introductionmentioning
confidence: 99%
“…21 It has also been shown that exposure to environmental carcinogens such as smoking and alcohol consumption increases the potential for chromosome breakage at fragile sites FRA3B and FRA16D in esophageal, non-small-cell lung and cutaneous squamous cancer. [21][22][23][24][25] Furthermore, we have recently described alterations on WWOX gene in 50% of oral squamous cell carcinomas. 26 Therefore, given that OLs have been associated with squamous carcinomas, we investigated whether molecular changes of the WWOX gene were present in these potentially malignant disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Re-expression of Fhit in Fhit-negative cancerderived cell lines increases sensitivity to mitomycin C (MMC), camptothecin (CPT), and cisplatin. 13,15,70,71 While the canonical role of each drug involves modulation of DNA topography to induce DNA damage, 16,17,[72][73][74] each agent also effects ROS production, and the production of ROS has been demonstrated to underlie the toxic effect of each compound.…”
Section: Discussionmentioning
confidence: 99%
“…HBEC3-TK is an immortalized bronchial epithelial cell line that has been used to study the consequences of gene inactivation in lung cancer. 13,35 These cells display normal epithelial morphology, are not transformed, have an intact p53 pathway, and have been used by others to study the pathogenesis of lung cancer. 35,36,39 We first determined that treatment of HBEC3-TK cells with 2 unique siRNAs robustly silences FHIT expression at both the mRNA and protein level ( Fig.…”
Section: Gene Expression Changes In Response To Fhit Knockdownmentioning
confidence: 99%
See 2 more Smart Citations